2016
DOI: 10.1182/blood.v128.22.4068.4068
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape, Clonal Evolution Patterns and Role of RAS Mutations in Relapsed Acute Lymphoblastic Leukemia

Abstract: Acute Lymphoblastic Leukemia (ALL) is the most common malignancy in children. Altogether 90% of pediatric ALL patients achieve a complete hematologic remission with current high dose combination chemotherapy and 80% of them remain leukemia free. However, the outcome for patients showing refractory disease or those whose leukemia relapses after an initial transient response remains disappointingly poor with cure rates of less than 40%. To investigate genetic drivers of relapse and resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Analysis of paired diagnosis and relapse ALL samples with increasingly broader and deeper genomic-sequencing methods has shown that classic Darwinian branching evolution of genomically distinct subclones is a hallmark of disease recurrence (4,5). At both diagnosis and relapse, a single neoplasm may contain multiple genetic subclones related to each other through complex evolutionary trajectories (4)(5)(6)(7). Although relapse may evolve from the predominant clone at diagnosis, in the majority of patients relapse arises from preexisting minor subclones within the diagnosis sample or from a rare ancestral clone (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of paired diagnosis and relapse ALL samples with increasingly broader and deeper genomic-sequencing methods has shown that classic Darwinian branching evolution of genomically distinct subclones is a hallmark of disease recurrence (4,5). At both diagnosis and relapse, a single neoplasm may contain multiple genetic subclones related to each other through complex evolutionary trajectories (4)(5)(6)(7). Although relapse may evolve from the predominant clone at diagnosis, in the majority of patients relapse arises from preexisting minor subclones within the diagnosis sample or from a rare ancestral clone (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…At both diagnosis and relapse, a single neoplasm may contain multiple genetic subclones related to each other through complex evolutionary trajectories (4)(5)(6)(7). Although relapse may evolve from the predominant clone at diagnosis, in the majority of patients relapse arises from preexisting minor subclones within the diagnosis sample or from a rare ancestral clone (4)(5)(6). Although the population-level genetic analyses upon which these conclusions are based rely on computational inference of their evolutionary relationships from analysis of bulk leukemic cells, resolution of leukemic subclones at clonal levels, either through isolation of subclones in xenografts or from single-cell analysis, has largely substantiated these predictions (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous aspects of glucocorticoid receptor function and regulation have been implicated in glucocorticoid resistance. These include decreased receptor auto-upregulation downstream of NOTCH1 signaling (Real et al, 2009), impaired glucocorticoid receptor activity resulting from posttranslational modifications induced by AKT (Piovan et al, 2013), defective glucocorticoid-induced transcriptional response secondary to mutations in important NR3C1 coactivators such as CREBBP (Mullighan et al, 2011), and relapse-associated mutations in NR3C1 (Oshima et al, 2016). All these mechanisms converge in defective glucocorticoid-induced transcription and consequent upregulation of BIM expression or impaired BIM-induced cell death, as in the case of mTOR signaling-mediated upregulation of MCL1, an antiapoptotic BCL2 family factor strongly antago-nistic of BIM function (Wei et al, 2006).…”
mentioning
confidence: 99%
“…These results are also pertinent to other hematological malignancies where the presence of leukemia-associated mutations in remission is associated with significantly increased risk of relapse and poor survival 31,37 . These data lead to the conclusion that it is imperative to identify alterations that induce therapeutic resistance in leukemia patients in the early stages of disease in order to properly guide individualized therapy with the goal of preventing disease relapse.…”
Section: Introductionmentioning
confidence: 85%